Investigating the corrosion activity of boron carbide and mica particle hybrid composites with an aluminum matrix prepared by stir casting - K. Velavan; K. Palanikumar; G. Perumal; N. Senthilkumar (Results in Engineering)
This study used the potentiodynamic polarization approach to evaluate the impact of mica content on the corrosion activity of aluminium alloy fortified with boron carbide (B4C) and mica-based hybrid aluminium metal matrix composites (HMMCs). Stir casting is adopted for preparing the HMMCs. In this investigation, mica is incorporated as reinforcement along with B4C, and Al6061 is utilized as the base metal. The HMMCs were prepared by varying the mica particles having weight fraction 0 %, 3 %, 4 %,5 %, 6 % and fixed weight fraction of 10 wt.% B4C. The dispersal of B4C+mica in the Al6061 matrix and the mechanism of corrosion occurring on the specimens' surface are seen with a scanning electron microscope (SEM). The potentiodynamic polarization test revealed that the corrosion current density (icorr) tends to decrease and linear polarization resistance (LPR) increase with increase of mica particles in AA6061+10 %B4C composites. It revealed that the Al6061+10 %B4C+6 %mica composite had a lower icorr value of 0.5289 mA/cm2 during the reverse scan, demonstrating a more stable passive layer and a slower dissolution rate than the other composites. Comparing Al6061+10B4C+6 %mica to other composites, it shows that the icorr value is around 1.3 folders lower and LPR value 1.2 folders higher than the Al6061+10 %B4C and 1.2 folders lower and 1.1 folders higher than Al6061+10 %B4C+3 %mica composites respectively. The findings from electrochemical impedance spectroscopy (EIS) test exposed that the charge transfer resistance (Rct) of Al6061+10B4C+6 %mica composite is 1.4 times higher than Al6061+10 %B4C and 1.3 times higher than the Al6061+10 %B4C+3 %mica composites. It indicates that Al6061+10B4C+6 %mica composite exhibits superior corrosion resistance than the other proportions of composites.